Naturally Acquired Antibody Responses to a Synthetic Malaria Antigen AS202.11 - Rebeka Nazareth; Pius Horumpende; Tolbert Sonda; Arnold Ndaro; Edson Mollel; Eliakim Paul; Emmanuel Athanase; Jaffu Chilongola (Journal of Tropical Medicine)
Background. A major challenge to malaria vaccine development is identification of protective epitopes and respective protective immune responses. Objective. To characterize naturally acquired Immunoglobulin G (IgG) responses to the synthetic peptide AS202.11, a malaria vaccine candidate. Methodology. This community based cross-sectional study enrolled 320 participants aged 1 year and above. Demographic information was recorded through interviews. Detection of P. falciparum infection was done by microscopy, malaria rapid diagnostic test, and polymerase chain reaction. ELISA was used to detect IgG antibody. Data was analyzed using STATA. Results. The overall AS202.11 IgG seropositivity was 78.8% (73.9–82.9). Seropositivity by age categories was ≤12 years [74.3% (67.4–80.2)], 13–40 years [85.3% (76.5–91.1)], and >40 years [82.6% (68.7–91.1)]. Compared to the ≤ 12-year-old group, aORs for the other groups were 2.22 (1.14–4.32), p=0.019, and 1.87 (0.81–4.35), p=0.143, for the 13–40-year-old and >40-year-old groups, respectively. The 13–40-year-old group had more seropositive individuals compared to the ≤ 12-year-old group. Conclusion. We report a high degree of recognition of AS202.11 by IgG elicited by field P. falciparum strains, suggesting its close similarity to native P. falciparum antigens and possible suitability of the peptide as a future malaria vaccine candidate.